Validation of the Uzbek version of the Kujala score in patients with patellofemoral disorders - M.Yu. Karimov, K.M. Mamatkulov, S.B. Madarakhimov, H.M. Asatullaev, N.R. Kobilov (International Journal of Advanced Science and Technology, 2020)
Resistance to these loads depends on a number of factors: the correct direction of movement, strength and controllability of the neuromuscular system, control of long-term loads, etc. The ends of nerve fibers are often located in the joints and paraarticular structures, as well as in the retinaculum, in the pes anserinus, in the synovial membrane, in the Goff bodies. Purpose of the study is translation of the Kujala questionnaire into Uzbek language, implementation in medical institutions of the Republic of Uzbekistan, expansion of opportunities for differential diagnosis of pain syndrome in the anterior part of the knee, assessment of short and long-term results of the treatment process using language skills, adaptation, validation. A finished copy of the questionnaire according to the results of this study indicated the reliability and validity of questionnaire to assess Uzbek language patients with patellofemoral disorders, regardless of age and gender. It was widely implemented to medical institutions of the Republic of Uzbekistan and accepted as easy-understandable, useful assessment tool for patients among orthopedists.